2014
DOI: 10.15832/tbd.44431
|View full text |Cite
|
Sign up to set email alerts
|

Additive Main Effects and Multiplicative Interactions (AMMI) Analysis of Grain Yield in Barley Genotypes Across Environments

Abstract: The study was carried out to analyze grain yield performances of nine varieties and sixteen advanced barley genotypes across eight environments of Southeastern Anatolia, Turkey, between 2003-2007 growing seasons. The experimental layout was randomized complete block design with four replications. Additive main effects and multiplicative interactions analysis (AMMI) revealed that the yield performances of genotypes were under the main environmental effects of genotype by environmental interactions. The first tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The high value in IPCA 1 was sufficient to study the total G×E interaction that was in accordance with the findings of Win et al (2017). Based on the performance of genotypes across different environments, AMMI 1 classified the genotypes as most stable and high yielding genotypes (G52, G29, and G43), less stable and high yielding genotypes (G37, G30, G14, and G11) and most stable and low yielding genotypes viz., G42, G22 and G4 as reported by Kilic (2014) in barley. From AMMI 2 biplot the highly interactive environment (E3) and genotypes (G34 and G14) were identified.…”
Section: Discussionsupporting
confidence: 51%
“…The high value in IPCA 1 was sufficient to study the total G×E interaction that was in accordance with the findings of Win et al (2017). Based on the performance of genotypes across different environments, AMMI 1 classified the genotypes as most stable and high yielding genotypes (G52, G29, and G43), less stable and high yielding genotypes (G37, G30, G14, and G11) and most stable and low yielding genotypes viz., G42, G22 and G4 as reported by Kilic (2014) in barley. From AMMI 2 biplot the highly interactive environment (E3) and genotypes (G34 and G14) were identified.…”
Section: Discussionsupporting
confidence: 51%
“…AMMI model 1 biplot is one of the many versions of AMMIs, basically for identifying high potential yield and stability (Olivoto et al, 2019). Kılıç(2014) reported that in AMMI 1 when the mean environments and genotypes are placed on the same lines that are parallel to the ordinate, it means that they have almost the same performance, but when the genotypes are placed on the right side of the center of the biplot, they show higher yield than those genotype at the left-hand side. These results are similar to our findings where all the genotypes like G8, and G13 located on the right side were the best genotypes for YPP, TNPP, HSW, FPW, LOS, and WOS.…”
Section: Ammi 1 Biplotsmentioning
confidence: 99%
“…The AMMI model 2 biplot is produced to make use of the environmental and genotypic scores of the first two AMMI components as reported by Vargas and Crossa (2000) and Kılıc( 2014). The IPCA1 and IPCA2 scores help to understand the function of genotype-by-environment interaction and the adaptability of the genotypes in the test environments.…”
Section: Ammi Modelmentioning
confidence: 99%
“…(2019) . While analyzing AMMI 1, Kılıç (2014) reported that the genotype and environment mean when positioned parallel to the ordinate indicates nearly equal performance. However, a higher yield is displayed by the genotypes positioned on the right side of the biplot’s center than by those on the left.…”
Section: Discussionmentioning
confidence: 99%